2017
DOI: 10.15294/kemas.v13i1.4174
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Risk Factor of Cardiovascular Disease Risk on Rural and Urban Population

Abstract: Cardiovascular disease is a global threat. This study aimed to obtain a description of cardiovascular disease pattern among rural and urban population in Ponorogo. Two locations were chosen to represent rural and urban area through cluster sampling. Cross sectional study design was chosen with a sample size of 350 respondents. The research instrument was adopted from WHO STEPS. Difference in prevalence between the two clusters were analyzed with ?2 test, with ?=0.05. The result showed that the prevalence smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
9
2
Order By: Relevance
“…This kind of heart work could later induce heart failure condition. Study by Rosjidi et al (2017) also support this findings by explaining that smoking, drinking alcohol, and consuming not fresh fruits could increase the risk factor of having cardiovascular diseases even leading to death. This phenomenon is having less attention to society particularly in smoker adolescents; because they assume that smoking only induce respiratory tract diseases.…”
Section: Methodsmentioning
confidence: 55%
“…This kind of heart work could later induce heart failure condition. Study by Rosjidi et al (2017) also support this findings by explaining that smoking, drinking alcohol, and consuming not fresh fruits could increase the risk factor of having cardiovascular diseases even leading to death. This phenomenon is having less attention to society particularly in smoker adolescents; because they assume that smoking only induce respiratory tract diseases.…”
Section: Methodsmentioning
confidence: 55%
“…In general, health factors are closely related to the life expectancy of a person. Besides, research conducted by Rosjidi, Isro'in, and Wahyuni (2017) also showed that risk factors for cardiovascular disease like hypertension, hypercholesterolemia, obesity, lack of physical activity and diabetes mellitus are more common in females than males. The studies with different findings above indicate that research on the relationship between life expectancy and gender still needs to be studied and carried out, especially in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…The major risk factors of PAD are similar to those of coronary artery disease and cerebrovascular disease, including older age, male, hypertension, diabetes mellitus, overweight/obesity, and cigarette smoking (Bennett, Silverman, Gill, & Lip, 2009). The prevalence of those risk factors is quite high among Indonesian population (Mihardja, Soetrisno, & Soegondo, 2014;Rachmi, Li, & Baur, 2017;Rosjidi, Isro'in, & Wahyuni, 2017;Harahap & Indrayana, 2018;Peltzer & Pengpid, 2018). Optimal management of those risk factors is crucial in the management of PAD and it may reduce overall cardiovascular mortality (Shammas, 2007).…”
Section: Methodsmentioning
confidence: 99%